2022
DOI: 10.3390/d14080654
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Chinese Longsnout Catfish (Leiocassis longirostris) in Four Farmed Populations Based on 20 New Microsatellite DNA Markers

Abstract: Freshwater aquaculture has a long and vibrant tradition in China. The Chinese longsnout catfish (Leiocassis longirostris) is a popular economic freshwater fish native to China. Understanding the genetic structure of L. longirostris populations is important for ensuring the efficacy of management practices and the sustainability of future increases in production. In this study, we used Illumina sequencing technology to isolate 20 novel polymorphic microsatellites from the genome of L. longirostris. These micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In Chinese longsnout catfish, one previous microsatellite study showed no significant genetic differentiation or systematic geographic pattern of this species in the Yangtze River [25]. Notably, high genetic diversity was observed in the cultured populations of Chinese longsnout catfish [26]. However, recently, the genetic diversity and differentiation of wild Chinese longsnout catfish have not been analyzed, which is vital to guide artificial proposition and release to restore wild populations and assess the impact of the ten-year fishing ban in the Yangtze River.…”
Section: Introductionmentioning
confidence: 81%
“…In Chinese longsnout catfish, one previous microsatellite study showed no significant genetic differentiation or systematic geographic pattern of this species in the Yangtze River [25]. Notably, high genetic diversity was observed in the cultured populations of Chinese longsnout catfish [26]. However, recently, the genetic diversity and differentiation of wild Chinese longsnout catfish have not been analyzed, which is vital to guide artificial proposition and release to restore wild populations and assess the impact of the ten-year fishing ban in the Yangtze River.…”
Section: Introductionmentioning
confidence: 81%
“…Microsatellites are continuously used in studies of genetic diversity in cultured stocks [ 22 , 412 , 413 ].…”
Section: Comparison Of Wild and Hatchery Stocksmentioning
confidence: 99%
“…A few types of molecular markers used in research associated with aquaculture and fisheries have been described over the last few decades decades [ 3 , 4 , 5 , 6 , 7 ]. Their applications in uncovering the differentiation of natural populations for the purposes of improved fishery management, population genetic structures and local adaptations for conservation biology purposes, identification of selected lines in aquaculture, analysis of kinship in the stocks and identification of individuals, finding quantitative trait loci (QTL) for the purposes of aquaculture, identification of taxa, food products, and forensics have been reported in a large number of papers [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%